Critical Discourse Analysis on Male Product Advertisements - Chandra, Jenifer; Buntoro, Ruth Shieren; Djuan, Devgandi; Linuwih, Endar Rachmawaty (English Department, Universitas Negeri Surabaya, 2023)
Beauty standard ideology or belief which is traditionally popularized by and through makeup products advertisement for women is not only influencing women across the globe but is now normalized in male products advertisements as well which convinces them to buy the product and which also has an impact on men’s belief of what an ideal masculine man is supposed to be. This study aims to find the “real man” standard ideology in male product advertisements. Moreover, the critical discourse analysis three-dimensional framework by Fairclough is applied in this research to show the “real man” ideology that is presented in male product advertisements especially the ones on social media where the latest ads can be found. Furthermore, we use descriptive qualitative research in analyzing and explaining 6 male products with a variety of types and brands. Data collection was carried out with structured interviews and advertisement observations. The findings of this study indicate that male product is very important to meet the main needs in overcoming problems in men. In addition, the main factor that is the reason for men to use male products is the demands of work or self-care, which is a representation of one's identity. According to the findings of this study, advertised men's products contain linguistic features that create ideology and manipulation for men, causing them to be interested in purchasing and using these products. Furthermore, men use these products because of stereotypes and public criteria for the appearance of a manly man.